Inter State Disparities in the Infrastructural Facilities - Kaur, Avinash; Kaur, Rajinder (Gyan Management Journal, 2017)
Infrastructure can be defined as comprising all those activities and services, whose contribution to the economy is not to generate the income within the sector itself, but also to provide sustenance and support to the income generation. The present study aims to assess the inter-state disparities in the infrastructural facilities and to study the socio-economic development of the states. The study further made an attempt to examine relationship between infrastructure and economic development. The study emphasized that infrastructure is considered as the pace setter of economic development and lack of proper infrastructural facilities will result in decline of economy's growth. The study concluded that there existed inter-state disparities in the infrastructural facilities and moreover, disparities existed in the socio-economic development among the states of India. The study suggested that the regional imbalances can be eroded by taking appropriate and proper policy initiatives by the Government. It is therefore required on the part of the Government to give serious attention to the administrative, regulatory, financial and institutional framework and should frame appropriate policies for infrastructural projects.
Keywords: Economic Development; Infrastructure; Disparities; Development; Index